The unity of consciousness : binding, integration, and dissociation (O. U. P., 2003)
Consciousness has many elements, from sensory experiences such as vision, audition, and bodily sensation, to nonsensory aspects such as volition, emotion, memory, and thought. The apparent unity of these elements is striking; all are presented to us as experiences of a single subject, and all seem to be contained within a unified field of experience. But this apparent unity raises many questions. How do diverse systems in the brain co-operate to produce a unified experience? Are there conditions under which this unity breaks down? Is conscious experience really unified at all?